PENILAIAN WARGA TERHADAP KELAYAKAN FASILITAS PUBLIK DI KARAWACI MENGGUNAKAN ALGORITMA DATA MINING NAIVE BAYES DENGAN FRAMEWORK RAPIDMINER - Ibnu Purnama Aji; Mohadib (CV. Multi Kreasi Media, 2024)
Rapid Miner is a software created by Dr. Markus Hofmann from the Blanchardstown Institute of Technology and Ralf Klinkenberg from rapid-i.com with a GUI (Graphical User Interface) display to make it easier for users to use this software. Karawaci District has a fairly large area with a fairly dense and large population. With the number of men 2018, 181329 and women 2019, 153793 the population must be balanced with the availability of public facilities/social facilities. The public facilities in question are the availability of good facilities for recreation, infrastructure, and cleaning facilities. However, in Karawaci District, there are still various problems in the process of assessing the feasibility of public facilities, causing delays in the delivery of information on the feasibility of these social facilities. To overcome this problem, researchers are interested in examining citizen assessments of the feasibility of public facilities in Karawaci using the Nave Bayes data mining algorithm with the Rapidminer framework. Data were analyzed using descriptive quantitative research methodology by describing journal references and sources based on related research. The results showed that, in a field trial using the rapid miner application in assessing the feasibility of public facilities in Karawaci by applying the nave Bayes algorithm data mining method and utilizing training data to generate the probability of each attribute with a different class, the calculation produces a value that can be calculated. optimized to determine the appropriate or unfit classification of public facilities and help evaluate the assessment to be more accurate.